Developing user-friendly ambulatory referrals: a quality improvement study in GI referral services at a large academic safety net hospital system - Aaron Gerard Issac; Wendy Du; Alix Youngblood; Wilhelmina Prinssen; Kelly Carroll; Robert Geller; Palak Patel; Bhavin Adhyaru; Jason Brown (BMC Health Services Research)
Abstract Background In the United States, more than a third of patients are referred to specialists each year; however, most of these referrals do not lead to completed appointments. At the Grady Health System (GHS), our large safety net hospital system, the initial gastroenterology (GI) referral process suffered from multiple inefficiencies, creating barriers to care. We aimed to improve GI referrals with both a triage and a direct-to-endoscopy program to relieve systemic barriers to GI care at GHS especially around colorectal cancer screening. Methods Given wait times for GI services and employee dissatisfaction with navigating patients through the referral process, a GI smart order set was built using the Epic electronic medical record. The process took 8 months and included automated anesthesia screening as well as periprocedural guidance on blood thinners. We measured time from placement of referral for screening colonoscopy to scheduling of the screening colonoscopy to assess improvement in wait times for GI services. Key results In our pre-implementation survey, 60% of providers placed at least one urgent referral a month, and 55% of providers were either somewhat or very dissatisfied with the referral process. This led to the creation of multiple unofficial and only partially successful bypasses to expedite GI care. With the new GI smart order set, there was a 93% reduction over 12 months in the time from providers screening colonoscopy referral request to procedure scheduling from an average of 422 to 28 days. In addition, overall rates of colorectal cancer screening increased approximately 6% from 43.5 to 49% since the order set was implemented. Conclusions This novel outpatient GI referral smart order set addressed multiple barriers to care and created a novel triage mechanism as well as a direct-to-endoscopy referral stream. This model can be used to improve triaging and increase access to GI and other specialist services.